Pleiotropic ZmICE1 Is an Important Transcriptional Regulator of Maize Endosperm Starch Biosynthesis - Liu, Hanmei; Wang, Yongbin; Liu, Lijun; Wei, Bin; Wang, Xieqin; Xiao, Qianlin; Li, Yangping; Ajayo, Babatope Samuel; Huang, Yubi (Frontiers in Plant Science, 2022)
Starch, the major component of cereal grains, affects crop yield and quality and is widely used in food and industrial applications. The biosynthesis of maize starch is a complex process involving a series of functional enzymes. However, the sophisticated regulatory mechanisms of starch biosynthetic genes have not been fully elaborated. The basic/helix-loop-helix (bHLH) transcription factors are widely distributed in eukaryotes and participate in many physiological processes. In this study, 202 bHLH encoding genes were identified in the maize genome by Blast method. ZmICE1 gene, which belongs to the ICE subfamily of the bHLH family, was obtained and expressed mainly in maize filling endosperm and co-expressed with 14 starch biosynthesis genes. Based on the comparative analyses across different plant species, we revealed that the gene structure and protein domains of the ICE subfamily were conserved between monocots and dicots, suggesting their functional conservation feature. Yeast activation and subcellular localization assay suggested that ZmICE1 had transcriptional activation activity and localized in the nucleus. Yeast one-hybrid assays confirmed that ZmICE1 could directly bind to the promoters of ZmSSIIa and ZmGBSSI. Transient gene expression analysis in maize endosperm revealed that ZmICE1 positively regulated the expression of ZmSSIIa, but inhibited the expression of ZmGBSSI. Our results indicated that ZmICE1 could function as a regulator of maize starch biosynthesis.